2017
DOI: 10.1038/srep44413
|View full text |Cite
|
Sign up to set email alerts
|

A cross-functional nanostructured platform based on carbon nanotube-Si hybrid junctions: where photon harvesting meets gas sensing

Abstract: A combination of the functionalities of carbon nanotube (CNT)-Si hybrid heterojunctions is presented as a novel method to steer the efficiency of the photovoltaic (PV) cell based on these junctions, and to increase the selectivity and sensitivity of the chemiresistor gas sensor operated with the p-doped CNT layer. The electrical characteristics of the junctions have been tracked by exposing the devices to oxidizing (NO2) and reducing (NH3) molecules. It is shown that when used as PV cells, the cell efficiency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 65 publications
0
5
0
1
Order By: Relevance
“…With respect to previous works [ 15 , 16 , 17 , 18 , 19 ], in the present paper, we focused on the possibility of using PV cells based on SWCNT/Si and MWCNT/Si as an ammonia gas sensor, taking advantage of the PV cell read-out scheme to measure changes in the PV cell electrical properties during exposure to the target gas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With respect to previous works [ 15 , 16 , 17 , 18 , 19 ], in the present paper, we focused on the possibility of using PV cells based on SWCNT/Si and MWCNT/Si as an ammonia gas sensor, taking advantage of the PV cell read-out scheme to measure changes in the PV cell electrical properties during exposure to the target gas.…”
Section: Discussionmentioning
confidence: 99%
“…In the rather heterogeneous set of devices proposed so far, hybrid carbon nanotube (CNT)/silicon (Si) heterostructures [ 6 , 7 , 8 , 9 , 10 , 11 , 12 ] have shown to be a promising platform to explore these concepts. Because of the sensitivity of electrical parameters to a flux of molecules over the CNT layer, it has also been suggested that these heterojunctions can be regarded as multifunctional devices, where the sensing capability can be combined with power generation of the junction [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ] with the aim of obtaining self-powered devices [ 15 , 21 , 22 ] after proper device engineering.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 10 a. The read-out circuit for the chemiresistive gas sensor is also quite straight-forward since only the current flowing through the resistor needs to be measured, which can be performed by placing a load resistor and reading the voltage across it [ 122 , 123 ]. The ease of chemiresistive gas sensor fabrication brings about the potential for their cost-efficient fabrication, ability of scaling, and eventual CMOS integration.…”
Section: Semiconductor-based Gas Sensor Typesmentioning
confidence: 99%
“…In addition, a large number of papers reported the possibility to suitably dope the SWCNT film to improve the NSH performances [12,13]. CNT/Si heterojunctions have been investigated for photovoltaic cells [10,11], chemical sensors [14], and photodetectors (PDs) [15][16][17][18][19][20][21][22][23][24]. Particularly interesting are the benefits that NSHs offer with respect to the Si p-n PDs currently dominating the market: e.g., a spectral operating range extending from near ultraviolet (UV) to near infrared (NIR), dimensions that can be reduced, low bias voltages to obtain high sensitivity, and fast response times [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%